Millennials' Preferences in Marketplace Buying - Muhammad Anasrulloh; Maria Agatha Sri W. H (Proceeding International Conference on Digital Education and Social Science, 2024)
Millennials, as the largest demographic group in the digital era, show unique preferences in marketplace purchasing behavior. This research aims to identify the factors that influence millennial purchasing decisions on the marketplace platform. The research method uses a quantitative approach with a survey involving 300 millennial respondents actively shopping online. The results of the analysis show that the factors of ease of access, competitive pricing, customer reviews, and discount promotions play a major role in influencing their preferences. In addition, aspects of user experience, such as intuitive application interface and transaction security, are also important priorities. Millennials tend to be more loyal to marketplaces that offer loyalty programs, such as cashback or reward points, which add value to their purchases. These findings indicate that marketplaces need to focus on developing innovative features that align with the needs of this generation, as well as improving personalization-based marketing strategies to strengthen customer engagement. This research provides insights for e-commerce businesses in designing effective marketing strategies that are oriented towards the needs of the millennial generation, which is the backbone of digital economic growth in Indonesia. Furthermore, this study recommends an in-depth exploration of consumer preferences.